2014
DOI: 10.4047/jap.2014.6.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Patients' knowledge and awareness of dental implants in a Turkish subpopulation

Abstract: PURPOSEThe purpose of this study was to evaluate the patients' knowledge on dental implants in a Turkish subpopulation.MATERIALS AND METHODSFive hundred twenty seven Turkish adults referred to Yeditepe University Faculty of Dentistry, Istanbul, Turkey, were presented with a questionnaire including 20 questions regarding the level of information and awareness about the dental implants. The data were collected and statistical analyses were performed with Chi square test to compare the descriptive data.RESULTSAmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
4
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 12 publications
9
32
4
7
Order By: Relevance
“…In the present study, 315 (66.73%) patients knew about FPD as replacement of missing teeth which is in contrast to studies conducted by Kumar et al, (13) Narayanan et al (14) and Tomruck et al (12) 205 (43.43%) patients had a knowledge about complete denture, which is similar to studies conducted by Tomruck et al (12) and Satpathy et al (10) 195 (41.31%) knew about all options of replacing missing teeth in present study, while only 29.5% knew about same options in study conducted by Kumar et al (13) 70 (14.83%) of subjects did not know any option, which is similar to study by Kohli et al (11%). (11) …”
Section: Ways To Replace the Missing Teethcontrasting
confidence: 90%
See 2 more Smart Citations
“…In the present study, 315 (66.73%) patients knew about FPD as replacement of missing teeth which is in contrast to studies conducted by Kumar et al, (13) Narayanan et al (14) and Tomruck et al (12) 205 (43.43%) patients had a knowledge about complete denture, which is similar to studies conducted by Tomruck et al (12) and Satpathy et al (10) 195 (41.31%) knew about all options of replacing missing teeth in present study, while only 29.5% knew about same options in study conducted by Kumar et al (13) 70 (14.83%) of subjects did not know any option, which is similar to study by Kohli et al (11%). (11) …”
Section: Ways To Replace the Missing Teethcontrasting
confidence: 90%
“…Out of 295 subjects who knew about implants, 120 (40.67%) got to know about implants from dentist which is similar to studies conducted by Satpathy et al, (10) Kumar et al (13) and Tomruck et al (12) 97 (32.88%) told friends and family as a source of information conducted by Santosh et al (15) and Khosyal et al (16) showed influence of friends and family as 10% and 6.1% respectively. TV, Newspaper advertisement as a source of information about implants was answered by 65(22.03%) subjects, which is in contrast to studies by Santosh et al (15) (5%) and Khosyal et al (16) (8.8%), while study by Kumar et al (13) has similar result as in the present study.…”
Section: Source Of Information About Implantssupporting
confidence: 81%
See 1 more Smart Citation
“…This finding has been reported in other studies. [2][3][4] These sources of information could be the reason fewer group I respondents correctly answered 2 of the 3 knowledge questions on the questionnaire, and this means that treating doctors will have to spend more time on correctly educating such persons should they become implant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmalarda hastaların farkındalık düzeyi %27,7 ile %77 arasında bulunmuştur. 1,2,[5][6][7]10,11 Çalışmamızda %66.7 olarak tespit edildi. Çalışmalarda dental implant farkındalığını farklı değerler alması katılımcıların farklı sosyal kültürel çevrelerden olmasından veya eğitim durumlarının farklı olmasından ya da çalışma yapılan popülasyonun sayılarındaki farklılıktan kaynaklanmış olabilir.…”
Section: Discussionunclassified